Next generation sequencing yields the complete mitochondrial genome of the darkfin hind Cephalopholis urodeta (Serranidae) from the Mischief Reef, South China Sea. Issue 1 (2nd January 2022) - Liu, Ning; Sun, Dianrong; Shan, Binbin; Liu, Yan; Wang, Liangming; Huang, Yingbang; Yang, Changping
Abstract: The complete mitochondrial genome of the Cephalopholis urodeta (Serranidae: Epinephelinae) was sequenced by next-generation sequencing method on the basis of one female specimen collected from coral reef areas at the Mischief Reef, South China Sea. The mitogenome is 16, 593 bp in length, including 13 protein-coding genes, 22 tRNA genes, two rRNA genes and a D-loop region. The overall content of A + T is 55.66%, which is significantly higher than the C + G content (44.34%). Among four bases, C shows the lowest frequency (15.99%). Phylogenetic tree based on the 13 protein-coding genes was constructed for analyzing the position of C. urodeta . The results provide useful insights into further studies on population genetics and phylogenetics of groupers.